Spinach yield and quality response to elevated soil carbon dioxide - Huang, Ying; Zhang, Xueyan; Ma, Xin (Frontiers in Plant Science, 2025)
IntroductionWith the widespread implementation of carbon capture and storage (CCS) projects, assessing the associated environmental risks has become increasingly important, particularly concerning crop responses to soil carbon dioxide (CO2) leakage. While previous studies have examined plant responses to soil CO2 stress, the implications for crop nutritional quality remain poorly characterized.MethodsA pot experiment was conducted in Shunyi, Beijing, during autumn 2023 to quantify the effects of CO2 leakage from CCS on the nutritional indicators of leafy vegetables. The experiment included four replicates per treatment, consisting of a control group (CK) and a CO2 leakage treatment group (1500 g·m-2·d-1, G1500). Spinach yield and quality were assessed under elevated soil CO2 conditions, with emphasis on vitamin C, vitamin E, cellulose, and oxalate content.ResultsProlonged exposure to high soil CO2 concentrations severely inhibited spinach growth, reducing leaf area, aboveground fresh weight, and root weight by 92.76%, 93.46%, and 95.83%, respectively. Chlorophyll b decreased by 35.48%, indicating impaired photosynthesis. Conversely, concentrations of vitamin C, vitamin E, and cellulose increased by 185.47%, 131.45%, and 315.03%, respectively, while oxalate content decreased by 43.08%. However, the severe biomass reduction led to an overall decline in total nutrient yield per plant.DiscussionThese findings demonstrate that soil CO2 leakage markedly inhibits growth and reduces total nutrient yield in leafy crops, despite the relative enrichment of certain nutritional components. The results highlight critical challenges to agricultural productivity and food quality in regions affected by CO2 leakage from CCS.